2010
DOI: 10.1080/07347332.2010.516811
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention to Improve Communication Between Breast Cancer Survivors and Their Physicians

Abstract: Breast cancer survivors often use clues to convey their concerns to their oncologists. The authors conducted a randomized trial of a communication coaching intervention in which 22 female breast cancer survivors were randomized to the coaching and 22 to treatment as usual. They hypothesized that the intervention would increase breast cancer self-efficacy, improve mood, and reduce fears of recurrence. Through a series of ANCOVAs they found that the intervention led to increases in self-efficacy. Changes in self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 36 publications
(39 reference statements)
0
27
0
Order By: Relevance
“…62 Five of the studies in this review also reported findings related to body image and the negative impact it may have on the partnered relationship for younger breast cancer survivors. 7,26,34,50,53 Premenopausal women were found to have significant concerns related to changes in their relationships (p<0.001), 34 and women 50 and younger experiencing greater body image concerns were associated with partner difficulty in understanding the feelings of the survivor (p<0.05).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…62 Five of the studies in this review also reported findings related to body image and the negative impact it may have on the partnered relationship for younger breast cancer survivors. 7,26,34,50,53 Premenopausal women were found to have significant concerns related to changes in their relationships (p<0.001), 34 and women 50 and younger experiencing greater body image concerns were associated with partner difficulty in understanding the feelings of the survivor (p<0.05).…”
Section: Resultsmentioning
confidence: 93%
“…62 As a result, younger women are at particular risk for psychological symptoms during and after treatment, including body image issues. In this synthesis of the literature, eleven of the studies evaluated only younger women (Table 1), 2,7,19,31,32,34,42,43,46,48,53 one of which compared younger women (ages 50 and younger) to healthy controls, finding that there were significantly worse total body image scores among the younger breast cancer survivors ( p <0.01).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, asking specific questions about QoL was expected to lead to more informative answers, providing clinicians with systematic overview of patients' well-being and care needs. It was also thought that asking a wide variety of questions could broaden the agenda of the consultation, facilitating the discussion of concerns relevant to the individual patient (Shields et al, 2010). However, in the field test patients often thought the QoL information they had provided was not discussed, reducing the perceived usefulness of the monitor.…”
Section: Discussionmentioning
confidence: 96%
“…Third, psychosocial interventions show promise in reducing anxiety, depressive symptoms, overall distress, and improving quality of life [38], which may promote appropriate follow-up care use among survivors. Studies have indicated peer counseling [39], communication coaching [40], use of imagery [41], and mindfulness-based stress reduction [42] show promise in improving psychosocial outcomes, particularly anxiety and distress, among breast cancer survivors. And lastly, individualized survivorship care plans are a promising approach to addressing low compliance with following-up care and surveillance recommendations among African American breast cancer survivors [43].…”
Section: Discussionmentioning
confidence: 99%